Anthropic Influences on the Quality of Underground Waters for Human Consumption in Russas, Ceará, Northeastern Brazil - Sousa, Joyce Shantala Fernandes de Oliveira; Gadelha, Amanda Aragão Moraes; Mendes, Luzia Suerlange Araújo dos Santos; Silva Neto, Cláudio Ângelo da; Salgueiro, Ana Rita; Cavalcante, Itabaraci Nazareno (Anuário do Instituto de Geociências, 2021)
In regions with semi-arid characteristics, groundwater is a precious source of water supply, mainly from alluvium, due to the decent quality of its waters. However, the sandy texture favors vulnerability, and the infiltration and percolation of fluids increase the risk of contamination of the aquifer in the presence of polluting sources. The population’s knowledge about these problems is still ephemeral, which can lead to the consumption of contaminated water, putting health at risk. Thus, research was conducted in the municipality of Russas – Ceará, to study the quality of groundwater, the possible polluting sources in the urban area, and assess the possible risks to human health. First, technical visits for reconnaissance and survey of information were conducted, such as possible polluting sources and situations of existing wells. The selection of wells to collect water followed criteria of proximity to polluting sources, well conditions, and, mainly, those linked to the use of water for human consumption. The result showed that 43% of the samples are above the limits proved by Brazilian legislation for turbidity, total hardness, TDS, sodium, chloride, and nitrate, while the others are within the standard. Concerning chlorides and nitrates, the concentrations show there is possibly a relationship with anthropic contaminants(agricultural area; domestic effluents) for the aquifer recharge areas and condition common problems to human health. Therefore, it is of paramount importance to continue research in Medical Geology that will enable the monitoring and future management of water quality of groundwater for the population.